Bunthato as a Cultural–Religious Bridge: An Exploratory Study of Its Role in Zakat, Infaq, and Sadaqah Practices in Gorontalo - Supandi Rahman; Hamid Pongoliu; Apolinário Magno; Sri Dewi Yusuf; Najamuddin Petta Solong; Luqmanul Hakiem Ajuna (Mimbar Agama Budaya, 2025)
This study explores bunthato, a Gorontalo cultural tradition in which the first income earned from daily labour is intentionally set aside for charitable purposes, and examines its relevance to strengthening zakat, infak, and sadaqah (ZIS) practices. The research seeks to understand how bunthato is interpreted and practised in contemporary Muslim life, and how its ethical values may inform culturally rooted ZIS governance. Data were collected over three months through in-depth interviews with 14 informants (religious leaders, customary leaders, market traders, fishermen, civil servants, and ZIS institutional representatives), supported by observation and document review. Data were thematically coded, and a conceptual model was developed through synthesis of emergent themes and supporting literature. Findings show that bunthato reflects a moral economy grounded in gratitude, solidarity, and amanah, functioning as a voluntary micro-philanthropy that complements institutional ZIS. The study proposes the Bunthato–ZIS Integrated Cultural Philanthropy Framework, positioning local wisdom as a bridge to accountable, culturally resonant Islamic philanthropy. Future research should pilot this framework to assess behavioural and institutional impact.